Kingdom of Lesotho : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The challenge of achieving broad-based growth in Lesotho is discussed. Economic growth is inconsistent. Lesotho is highly dependent on trade with South Africa. The sources of growth in Lesotho using a social accounting matrix model and a growth-accounting framework are outlined. The main constraints to growth and private investment and current policy initiative to promote broad-based growth and private investment are analyzed. The various methods employed suggest that there is neither external stability nor significant evidence of exchange rate misalignment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet